Films and friends starting and maintaining a movie group - Vandervelde, Maryanne (New York Thomas Dunne Books, 2004)
If you've wanted to be in a film club but didn't know how to get started, choose films, and keep discussions going, this book is for you. Here, Maryanne Vandervelde offers advice on how to deal with problems that might arise, including unforeseen pitfalls, uncooperative discussants, and scheduling conflicts.

But it's the close friendships formed and fascinating discussions over the years that explain why her group is still going strong more than seven years after it was founded. She has compiled reflections on what they have learned, a breakdown of all movies they've discussed, and suggestions for movie rentals, with accompanying issues and discussion topic to get the ball rolling.

Fun and informative. Films and Friends is a warm and entertaining guide full of everything you need to know about starting and maintaining a movie group.
Keywords: Motion pictures -- Societies, etc